Determinants of Post-Vaccination Antibody Titers to PPR Vaccine in Sheep: A Cross-Sectional Statistical Study - Abdulla, Osama A. (American Journal of Biomedicine and Pharmacy, 2025)
Peste des Petits Ruminants (PPR) is an acute, highly contagious fatal viral disease of small ruminants and remains to be a limiting factor for productivity in the developing countries including Iraq. Vaccination remains the key strategy for controlling PPR and post-vaccination antibody responses can differ considerably between animals, which could influence both individual and herd protection levels. The objective of this study was to determine the animal- and management-related factors influencing antibody titers against PPR in sheep vaccinated. A cross-sectional study was carried out on population of Baghdad governorate, Iraq from March to May, 2025. One hundred and twenty clinically healthy sheep were selected at random from four flocks. Blood samples were taken between 21 and 35 days after receiving a commercial live attenuated PPR vaccine. Serum antibody titers were determined by indirect ELISA and predictor variables included age, sex, body condition score (BCS), deworming status, size of flock and history of previous vaccination. The descriptive statistics were produced and univariate analyses were performed followed by multiple linear regression for the determination of independent factors of AB response. The mean antibody titer (as S/P ratio) was 0.63 ± 0.18 overall. Adult sheep and those scored positive (≥3) had significantly higher levels of antibody when compared to lambs and sheep in poor BCS (p < 0.05). Dewormed animals also presented the highest responses, and the absence of deworming was associated with lower titers. Booster history influenced antibody levels, in a positive way. There was no statistically significant difference between genders or flock-sizes. Multivariate analysis retained adult age (β = +0.12), increased BCS (β = +0.10), repeated vaccination (β = +0.09) as independent positive predictor, and no deworming as negative predictor (β = −0.08). These results highlight the need for proper nutrition management, parasite control and booster vaccinations in order to maximize the vaccine-induced immunity. Integration of these interventions in routine flock health programs can enhance the control of PPR and may facilitate small ruminant disease control and eradication activities in Iraq, and elsewhere.